Biodegradation of Methyl Parathion Using Pseudomonas stutzeri (MTCC 2643) - S, Archana; A, Surendran; A.J, Thatheyus (Journal of Biotechnology and Biomedical Science, 2020)
Pesticides applied in agricultural fields for crop protection result in the contamination of the environment. They also affect the flora and fauna as well as the quality of air, water and soil. Hence their remediation is of concern. Among different strategies available, microbial remediation is cost effective and ecofriendly. The present work is designed to test the efficiency of Pseudomonas stutzeri, a bacterial strain obtained from MTCC, IMTECH, Chandigarh, India. After treating with 50, 100, 150 and 200 ppm of methyl parathion, parameters like, orthophosphate released, pH and turbidity changes were monitored upto thirty hours. Degradation of 200 ppm concentration was confirmed by UV-Visible spectrophotometry and HPLC analysis. This strain effectively degraded methyl parathion and it can be used in the remediation of contaminated agricultural fields.
Keywords: Methyl parathion; Pseudomonas stutzeri; Biodegradation; Pesticide; Bioremediation.